TRILINGUAL FOLKSONGS BOOK: TRANSLATING TANA LUWU FOLKSONGS INTO AN ENGLISH-INDONESIAN SONGBOOK - Sahraini; St. Hartina; Husnaini; Syarani, Novi (English Language Teaching Methodology, 2024)
Translating folk songs into English or another language can play a crucial role in ensuring the survival of these traditions in a globalized world. This research attempted to design of the translation of Tana Luwu folksongs into Indonesian-English songs book. The research question of this research is “How is the appropriate design of English-Indonesian Translation book of Tana Luwu folksongs?”. The participants of this research were students at SMAN 3 Luwu in tenth grade. The research was Research and Development (R&D) utilizing the 4D model. It consists of defining, designing, developing, and disseminating. This research used several instrumens: a questionnaire and interview for need analysis, an experts’ validation, and a questionnaire for students’ and teachers’ perceptions. The researcher employed Nida & Taber's (2003) Translation theory to interpret the song's figurative language. The outcomes of this research is Trilingual folksongs book which consists 11 compilation of Tana Luwu Folksongs translated in English and Indonesian, then equipped with vocabulary list and barcode for each song. In this research, three experts were involved in validating the product, therefore the research shows that based on expert validation and student and teacher perceptions, this research product is feasible to use globally. Folk song translations book can be a way for these people to re-establish a relationship with their heritage by giving them an opportunity to experiencing and comprehending their cultural origins in a language that is more familiar to them.